Dispensasi Kawin dan Perceraian Usia Anak: antara Realitas Sosial dan Tekstual Hakim - Yulmitra Handayani; Fika Aufani Kumala; Muhammad Al Mansur; Juwandi (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2023)
This study responds to the Determination of marriage permits by the Jember Religious Court which was accompanied by a Divorce Decision submitted by the same party in a short period of time. Child divorce is the result of hasty marriages, without knowing more about the holistic and substantive meaning of marriage. Methodologically, this study uses a sociological normative approach with primary data on the decisions and decisions of judges at the Jember Religious Court and reduces various cases of child marriage which result in divorce at a young age. The result is that the judge uses the diction "worried" in each determination and tends not to represent urgent events or events for marriage. In the end, not a few cases of divorce/divorce were filed by the party who originally applied for a marriage permit. Therefore, it is very necessary to make new reasoning and patterns that are limiting in nature, so that it is expected to be able to minimize divorce at a young age complete with the consequences it bears.)